KECEMASAN PADA DEWASA TUA (LANSIA) DALAM MENGHADAPI KEMATIAN - Widia Sri Ardias; Putri Intan Purwari (Universitas Islam Negeri Imam Bonjol Padang, 2019)
This study aims to look at the relationship between religiosity and death in older adults. The subject selection technique was done by purposive sampling consisting of 48 elderly adults. This study uses a non experimental quantitative approach. Hypothesis testing is done through the Pearson product moment correlation statistical test using the SPSS application. This study proves that there is a negative linear relationship between religiosity and anxiety of death in older adults. this proves that religious older adults have lower anxiety in the face of death. On the other hand, older adults with a low religious level proved to be more anxious in facing death.